2006
DOI: 10.3133/sir20055084
|View full text |Cite
|
Sign up to set email alerts
|

Physical and hydrochemical evidence of lake leakage near Jim Woodruff Lock and Dam and of ground-water inflow to Lake Seminole, and an assessment of karst features in and near the lake, southwestern Georgia and northwestern Florida

Abstract: Boat-mounted acoustic Doppler current profiling apparatus in use near the River Boil; looking north from Apalachicola River toward Jim Woodruff Lock and Dam in background. Photograph by Lynn J. Torak, U.S. Geological Survey River Boil on Apalachicola River, about 900 feet downstream of Jim Woodruff Lock and Dam, near Chattahoochee, Florida. Photograph by Lynn J. Torak, U.S. Geological Survey Vortex flow entering sinkhole in the bottom on Lake Seminole at a depth from about 8 to 10 feet, located along the weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The Apalachicola River has the largest discharge of all the rivers in Florida, accounting for roughly one-third of freshwater runoff on the west coast of Florida [223]. The Apalachicola River begins at The Jim Woodruff Lock and Dam, flows towards the south, and eventually discharges to the shallow estuarine Apalachicola Bay, where it is the primary source of freshwater [224,225]. The Apalachicola River has a wide floodplain and is subject to variable seasonal flow [77,226].…”
Section: Climate-change Influences On Runoff and Sediment Loads To Ap...mentioning
confidence: 99%
“…The Apalachicola River has the largest discharge of all the rivers in Florida, accounting for roughly one-third of freshwater runoff on the west coast of Florida [223]. The Apalachicola River begins at The Jim Woodruff Lock and Dam, flows towards the south, and eventually discharges to the shallow estuarine Apalachicola Bay, where it is the primary source of freshwater [224,225]. The Apalachicola River has a wide floodplain and is subject to variable seasonal flow [77,226].…”
Section: Climate-change Influences On Runoff and Sediment Loads To Ap...mentioning
confidence: 99%
“…An alternative approach is to use oxygen and hydrogen isotopes because lake water is generally isotopically heavier than groundwater due to evaporation (Krabbenhoft et al 1990). It has been demonstrated that the isotopes are highly effective for identifying a hydraulic connection between sinkhole lakes and karst springs (Criss et al 2001; Torak et al 2006; Day and Poeter 2009; Leng et al 2010) and between sinking streams and karst springs (Greene 1997; Frisbee et al 2019; Rusjan et al 2019). While isotope approaches are less quantitative than dye tracing approaches (especially on the aspects of estimating hydrogeological parameters of solute transport), isotope approaches have an advantage that isotope ratios can be measured from water samples collected over a long period of time, for example, months and potentially years.…”
Section: Introductionmentioning
confidence: 99%
“…These tributaries drain a combined land area of 46 141 km 2 . Groundwater also contributes a substantial component of flow into the lake (Torak et al 2006). Concentrations of nutrients within the lake were measured monthly over a 12 mo period during a study by McEntire (2009).…”
Section: Site Descriptionmentioning
confidence: 99%